SEQUENCE POLYMORPHISMS OF FOUR CHLOROPLAST GENES IN FOUR ACACIA SPECIES - Anthonius Y.P.B.C. Widyatmoko; Susumu Shiraishi (Indonesian Journal of Forestry Research, 2011)
Sequence polymorphisms among and within four Acacia species,  A. aulacocarpa, A. auriculiformis, A. crassicarpa, and A. mangium, were investigated using four chloroplast DNA genes (atpA, petA, rbcL, and rpoA). The phylogenetic relationship among these species is discussed in light of the results of the sequence information. No intraspecific sequence variation was found in the four genes of the four species, and a conservative rate of mutation of the chloroplast DNA genes was also confirmed in the Acacia species. In the atpA and petA of the four genes, all four species possessed identical sequences, and no sequence variation was found among the four Acacia species. In the rbcL and rpoA genes, however, sequence polymorphisms were revealed among these species. Acacia aulacocarpa and A. crassicarpa shared an identical sequence, and A. auriculiformis and A. mangium also showed no sequence variation.  The fact that A. mangium and A. auriculiformis shared identical sequences as did A. aulacocarpa and A. crassicarpa indicated that the two respective species were extremely closely related. Although a putative natural hybrid of A. aulacocarpa and A. auriculiformis has been reported, our results suggested that natural hybridization should be further verified using molecular markers.